The Influence of Video Marketing, User Generated Content on Purchase Intention through Brand Awareness as Intervening Variables - Nur Diana Khalidah; Siti Asiyah; M. Ridwan Basalamah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims to determine the development of Digital Marketing in Sumenep Regency, especially in the Jamjamyeon business, namely by analyzing the effect of Video Marketing and User Generated Content on Purchase Intention both directly and indirectly through Brand Awareness as an intervening variable. The sample in this study was determined by purposive sampling technique. The type of data in this study is primary data with a guttman scale. The data collection technique used a questionnaire and the data analysis method used in this study was the Partial Least Square (PLS) method. The results of the study show that Video Marketing has no effect on Purchase Intention, but Video Marketing has an effect on Brand Awareness. User Generated Content has no influence on Purchase Intention and Brand Awareness. And Brand Awareness has no effect on Purchase Intention. As for the indirect effect, Brand Awareness is unable to mediate the effect of Video Marketing and User Generated Content on Purchase Intention.